Decolonial Thinking and Configuration of Decolonial Competencies - Ortiz Ocaña, Alexander Luis (2019)
There is no doubt that since the end of the 20th century and the beginning of the 21st century, decolonial sciences are emerging. Currently, an epistemic migration is occurring from historic-hermeneutic sciences and socio-critic sciences towards decolonial sciences. This process has not been oblivious to the sciences of education. They have joined the decolonial turn. Thus, pedagogy has also joined the process. Pedagogy is also rotating. And it is doing its turn in a decolonial code. For all of the above, it is necessary to not ignore the urgencies that summon us and the emergencies that invite us to the epistemological resistance, starting from an epistemic disobedience. Decolonizing education, moving towards the decoloniality of curriculum and proposing a decolonial curriculum, is now an imperative. This is only possible if we turn together with the decolonial turn of pedagogy. Precisely, the reflection that we are discussing today on decoloniality and decolonial pedagogy, constitute this laudable effort and contribute to the configuration of decolonial/border thinking, as a foundation of “other” competencies: decolonial competencies supported by decolonial thought and Critical Latin-American -and Caribean- Theory.